Cladistics of some rattans (Calamus spp.) from Central Sulawesi based on physical and mechanical characteristic of stems - ANDI TANRA TELLU (Biodiversitas Journal of Biological Diversity, 2006)
The research of the physical and mechanical characteristic of rattans stem of 10 species of the genus Calamus from Bancea Nature Reserve and Lore Lindu National Park in Central Sulawesi had been conducted. The aims of this research were to describe phylogenetic relationship of those species based on physical and mechanical characteristic with cladistic approach (cladogram). The research had been used descriptive method, i.e. specific gravity, parallel attracting firmness of fiber, firmness stress parallels of flex firmness, and fiber/static curve. It was reconciled with standard of ASTM D no 143-52 with a few which has modified. The data was analyzed by ANOVA. The resultindicated that the mechanical and physical characteristic of Calamus rattan can be made as distinguishing evidences. It can be compiled by a new classification in the form of cladistic (classification of numeric) as complement of previous classification.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: rattan, Calamus, cladistics, physic, mechanics.